Altruistic indulgence: people voluntarily consume high-calorie foods to make other people feel comfortable and pleasant - Yi, Youjae; Lee, Jacob C.; Kim, Saetbyeol (Social influence, 2018)
We explored a novel phenomenon where people in certain social contexts voluntarily consume high-calorie foods with the altruistic motive of making other people feel comfortable and pleasant. We hypothesized that people are likely to choose a high-calorie food, especially around others with whom they have communal relationships (e.g., friends), because of the desire to induce in others feelings of pleasantness rather than guilt. A field study at a café shows that this phenomenon emerges in the real world, and a scenario-based experiment supports our altruistic account with mediation analyses. The alternative explanation of a social acceptance account is ruled out.